Pulmonary exposure to renewable diesel exhaust particles alters protein expression and toxicity profiles in bronchoalveolar lavage fluid and plasma of mice - Sarah McCarrick; Vilhelm Malmborg; Louise Gren; Pernille Høgh Danielsen; Martin Tunér; Lena Palmberg; Karin Broberg; Joakim Pagels; Ulla Vogel; Anda R. Gliga (Archives of Toxicology, 2025)
Exposure to diesel exhaust is associated with increased risk of cardiovascular and lung disease. Substituting petroleum diesel with renewable diesel can alter emission properties but the potential health effects remain unclear. This study aimed to explore toxicity and underlying mechanisms of diesel exhaust from renewable fuels. Using proximity extension assay (Olink), 92 proteins linked to inflammation, cardiovascular function, and cancer were analyzed in bronchoalveolar lavage fluid (BALF) and plasma in mice 1 day after pulmonary exposure to exhaust particles at doses of 6, 18, and 54 µg/mouse. Particles were generated from combustion of renewable (rapeseed methyl ester, RME13, hydrogen-treated vegetable oil, HVO13; both at 13% O 2 engine intake) and petroleum diesel (MK1 ultra-low-sulfur diesel at 13% and 17% O 2 intake; DEP13 and DEP17). We identified positive dose–response relationships between exposure and proteins in BALF using linear models: 33 proteins for HVO13, 24 for DEP17, 22 for DEP13, and 12 for RME13 ( p value e.g., CCL2, CXCL1, CCL3L3, CSF2, IL1A) correlated ( r s ≥ 0.5) with neutrophil cell count and DNA damage in BAL cells. Interestingly, plasma protein profiles were only affected by RME13 and, to lesser extent, by DEP13. Overall, we identified inflammation-related changes in the BALF as a common toxic mechanism for the combustion particles. Our protein-based approach enables sensitive detection of inflammatory protein changes across different matrices enhancing understanding of exhaust particle toxicity.